2021
DOI: 10.1002/app.51258
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fibrillated poly(tetrafluoroethylene) on microcellular foaming of polyamide 6 in the presence of supercriticalCO2

Abstract: In this article, PA6/poly(tetrafluoroethylene) (PTFE) composites were prepared by internal mixer with high rotor speed. The existence of PTFE nano‐fibrillation network structure was observed by scanning electron microscopy (SEM) analysis. The effect of PTFE on crystallization and rheological behavior of PA6 was evaluated. The result showed that the PTFE fibrils improved the crystallization properties of PA6 and do not change the crystal structure. The PTFE effectively enhanced the melt strength of PA6 by fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…26,27 PTFE fibers have effectively improved the crystallization and melt strength performances of PA6. 28 Wang et al 29 also demonstrated that PTFE fiber networks significantly improved the melt viscoelasticity of polybutylene terephthalate (PBT) wherein the fibers promoted crystallization kinetics and changed the PBT crystallization structure. Meanwhile, nascent PTFE is a highly crystalline polymer with low chain entanglement density which can undergo fibrillation during matrix shearing.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 PTFE fibers have effectively improved the crystallization and melt strength performances of PA6. 28 Wang et al 29 also demonstrated that PTFE fiber networks significantly improved the melt viscoelasticity of polybutylene terephthalate (PBT) wherein the fibers promoted crystallization kinetics and changed the PBT crystallization structure. Meanwhile, nascent PTFE is a highly crystalline polymer with low chain entanglement density which can undergo fibrillation during matrix shearing.…”
Section: Introductionmentioning
confidence: 99%
“…After fiber addition, the cell diameters decreased from 22 to 2 μm and cell density increased by three orders of magnitude. 26,27 Peng et al added PTFE to poly(propylene carbonate) (PPC) and polystyrene (PS) using a three-screw extrusion method. The cell density of PPC increased by four orders of magnitude and the PS/PPC/PTFE foam exhibited excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that PTFE fibers in polyethylene terephthalate (PET) and PA6 effectively promote the formation of cellular structures of the resulting PET/PTFE and PA6/PTFE foams. After fiber addition, the cell diameters decreased from 22 to 2 μm and cell density increased by three orders of magnitude 26,27 . Peng et al added PTFE to poly(propylene carbonate) (PPC) and polystyrene (PS) using a three‐screw extrusion method.…”
Section: Introductionmentioning
confidence: 99%
“…However, its poor notched impact toughness (especially at low temperatures) restricts its overall performance, which limits its applications in modern plastic industries and newly emerging fields [ 5 , 6 , 7 , 8 , 9 ], e.g., wearable fabrics [ 4 ], self-supporting water purification films [ 9 ], and nanofiltration membrane [ 7 ], etc. To solve this issue, PA6 matrix has been modified by reinforcing materials, such as hydrogenated acrylonitrile-butadiene-styrene (ABS) [ 10 ], styrene-co-acrylonitrile (SAN) [ 11 ], hydrogenated styrene-butadiene-styrene (SEBS) [ 12 ], polyamide 66 [ 13 ], poly(tetrafluoroethylene) (PTFE) [ 14 ], and thermotropic liquid crystalline polymer (TLCP) [ 15 ], etc. For those reinforcing monomers or polymers, they have similar functional groups to that of PA6, which is advantageous to obtain compatible polymer composites to overcome the phase separation problem at the interface of PA6 and reinforcing additives through chemical and physical interactions or adhesions between them.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, among those polymer modifiers [ 10 , 11 , 12 , 13 , 14 , 15 ], TLCP is one promising choice. Because of the peculiar rigid-rod chemical structures, TLCP in the solid form possesses many unique properties, e. g., low melt viscosity and high mechanical modulus in the oriented direction.…”
Section: Introductionmentioning
confidence: 99%